SM22 a Plasma Biomarker for Human Transmural Intestinal Ischemia. Issue 1 (July 2018) - Schellekens, Dirk H. S. M.; Reisinger, Kostan W.; Lenaerts, Kaatje; Hadfoune, M'hamed; Olde Damink, Steven W.; Buurman, Wim A.; Dejong, Cornelis H. C.; Derikx, Joep P. M.
Abstract : Objective: To evaluate the diagnostic potential of smooth muscle protein of 22 kDa (SM22) as plasma biomarker for the detection of transmural intestinal ischemia. Background: Acute mesenteric ischemia is an abdominal emergency requiring rapid diagnosis and treatment. Especially, detection of transmural damage is imperative because it mandates emergency surgery. Since early clinical and radiological signs are nonspecific, there is an urgent need for accurate biomarkers. SM22 is a potential marker for transmural damage because of its abundant expression in intestinal smooth muscles. Methods: SM22 concentrations were measured using a newly built enzyme-linked immunosorbent assay. SM22 release was assessed in plasma and intestinal tissue of rats subjected to intestinal ischemia. Blood and tissue were sampled at baseline and followed up to 24 hours of ischemia. Next, organ-specific SM22 arteriovenous concentration differences were studied in both rats and patients. Finally, plasma from patients with intestinal ischemia, other acute abdominal complaints, and healthy volunteers were tested for SM22. Results: SM22 concentrations were significantly elevated in rats from 4 hours of ischemia onwards. Furthermore, SM22 plasma concentrations closely paralleled the histological increasing degree of intestinal smooth muscle damage. Arteriovenous calculations showed that SM22 was specifically released by the intestines and renally cleared. First data of SM22 release in man demonstrated that patients with transmural intestinal ischemia had significantly higher plasma SM22 levels than patients with only ischemic mucosal injury, other acute abdominal diseases, or healthy controls. Conclusions: This study shows that SM22 is released into the circulation upon severe ischemia of the intestinal muscle layers. Plasma levels of SM22 are potentially useful for the detection of transmural intestinal damage. Abstract : Supplemental Digital Content is available in the text